Accurate OH maser positions from SPLASH: Understanding the origins of OH masers with an unbiased survey - Qiao, Haihua (Curtin University, 2017)
This thesis investigated the accurate positions of ground-state OH masers with the ATCA. All ATCA observations have been completed. 215 OH maser sites in the pilot region have been fully reduced and published. One planetary nebula site has been detected with Zeeman splitting at 1720 MHz, which is used to infer the magnetic fields. Preliminary result in the Galactic Centre region has been briefly listed. Further work related to this project has also been introduced.